The Impact of E-Learning Practices and Assessment Competency on Academic Performance: A Structural Equation Modeling Approach - Leuwol, Ferdinand Salaomo; Lasaiba, Mohammad Amin (AL-ISHLAH: Jurnal Pendidikan, 2026)
E-learning has become an essential component of higher education, yet its contribution to academic performance depends not only on digital learning practices but also on students’ assessment competency. This study examined the effects of e-learning practices, assessment knowledge, assessment skills, and attitudes toward assessment on undergraduate students’ academic performance. A quantitative correlational survey design was employed involving 440 undergraduate students from four teacher education programs at Pattimura University, Indonesia. Data were collected using a structured questionnaire measuring e-learning practices and three dimensions of assessment competency: knowledge, skills, and attitudes. Students’ academic performance was measured using Grade Point Average (GPA). The data were analyzed using Structural Equation Modeling to evaluate the measurement model and test the hypothesized relationships among variables. The findings showed that e-learning practices had a positive and significant effect on academic performance. Assessment knowledge, assessment skills, and attitudes toward assessment also significantly predicted students’ GPA. The measurement model demonstrated acceptable reliability and convergent validity, indicating that the indicators adequately represented the proposed constructs. The structural model confirmed that both digital learning practices and assessment competency contributed to students’ academic achievement. These findings suggest that effective e-learning implementation should be supported by students’ ability to understand assessment criteria, use feedback, and develop positive attitudes toward assessment. Universities should strengthen digital learning systems while integrating assessment literacy into teaching and learning practices. The study provides empirical evidence for improving technology-supported learning in higher education, particularly in developing contexts where e-learning quality and assessment capacity remain uneven.